Stackelberg security games: Looking beyond a decade of success - SINHA, Arunesh (Institutional Knowledge at Singapore Management University, 2018)
The Stackelberg Security Game (SSG) model has been immensely influential in security research since it was introduced roughly a decade ago. Furthermore, deployed SSG-based applications are one of most successful examples of game theory applications in the real world. We present a broad survey of recent technical advances in SSG and related literature, and then look to the future by highlighting the new potential applications and open research problems in SSG.